2014
DOI: 10.1017/s1751731113001833
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different levels of crude glycerol on the morphology and some pathogenic bacteria of the small intestine in male broilers

Abstract: The gut health of poultry is closely associated with feeds and feeding. The experiment was conducted to the effect of crude glycerol addition to diets of male broilers on the bacterial microflora and morphology of their small intestines (duodenum, jejunum and ileum). A total of 120 Ross 308 broiler chicks received diets containing 0% (GLY 0), 4% (GLY 4) or 8% (GLY 8) crude glycerol for 42 days. The presence of Coliform bacteria and Enterobacteria was reduced in the duodenal tract of the broilers of GLY 4 (P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
(31 reference statements)
1
9
0
Order By: Relevance
“…Widening of villus indicates less nutrient absorption area and probably also greater amount of gut-associated immune tissue proliferation and accumulation in the villus, which is another indication of compromised gut heath. The structural change in GBF birds confirmed that gut barrier failure was occurring in GBF birds, which may be associated with the poor performance in this study and is consistent with a previous study ( 49 ).…”
Section: Discussionsupporting
confidence: 92%
“…Widening of villus indicates less nutrient absorption area and probably also greater amount of gut-associated immune tissue proliferation and accumulation in the villus, which is another indication of compromised gut heath. The structural change in GBF birds confirmed that gut barrier failure was occurring in GBF birds, which may be associated with the poor performance in this study and is consistent with a previous study ( 49 ).…”
Section: Discussionsupporting
confidence: 92%
“…Impaired TJs also contribute to diarrhea by causing intestinal leakage via the flux mechanism (22). In addition, a previous study reported that an impaired TJ barrier is consistently associated with growth performance (23). This demonstrates that low TJ protein levels allow the entry of intraluminal antigens into the systemic circulation, resulting in poor intestinal permeability.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain the final value of the ISI index, the IF of each alteration was multiplied by the respective score number, and the results of all alterations were summed according to the formula ISI = Σ(IF × S), where IF is the impact factor, and S is the score. Additionally, other morphometric measurements including villus height (from the base of the intestinal mucosa to the tip of the villus excluding the intestinal crypt), crypt depth (from the base upward to the region of transition between the crypt and villi), and villus height-to-crypt depth ratio were evaluated ( Ozdogan et al., 2014 ).…”
Section: Methodsmentioning
confidence: 99%